0139 SUVN-G3031, A Potent and Selective Histamine H3 Receptor Inverse Agonist - Phase-2 Investigational New Drug for the Treatment of Narcolepsy - Differentiating Factors with Competitor Clinical Candidates. (12th April 2019) - Nirogi, Ramakrishna; Bhyrapuneni, Gopinadh; Abraham, Renny; Subramanian, Ramkumar; Goyal, Vinod Kumar; Pandey, Santosh Kumar; Badange, Rajesh; Shinde, Anil
Abstract: Introduction: SUVN-G3031 is one of the potent H3 receptor (H3R) inverse agonist in the clinical development for the treatment of narcolepsy with or without cataplexy. Phase-1 evaluation for safety, tolerability and pharmacokinetics, and long term safety studies in animals has been successfully completed. Methods: Extensive nonclinical profiling was carried out for SUVN-G3031 and H3R receptor antagonists/inverse agonists that are in active clinical development for the treatment of sleep related disorders. The nonclinical parameters like binding affinity at human and rat H3R, selectivity profiling, in-vivo and in-vitro ADME features, nonclinical efficacy, neurochemistry and safety were evaluated. Results: SUVN-G3031 has no inter-species variation in binding affinity at H3R with >100 fold selectivity. Unlike competitor compound, SUVN-G3031 has no binding affinity at sigma 1 and 2 receptor up to the highest tested concentration of 10 µM. SUVN-G3031 has no inhibition and induction liability against major CYP isoforms and is neither an inhibitor nor a substrate of major uptake transporters. SUVN-G3031 has moderate plasma protein binding. SUVN-G3031 has superior oral pharmacokinetic and brain penetration properties in rat than the competitor compound. EEG study indicated wake promoting profile of SUVN-G3031 is superior than compounds of this class active in clinical development. SUVN-G3031 showed negligible affinity towards hERG channel (IC50 > 10 µM) and had no effects on any ECG parameters in dog telemetry study. SUVN-G3031 showed no convulsions or signs of other CNS safety. Unlike competitor compound, SUVN-G3031 has no adverse effects on fertility and embryo-fetal development up to highest tested doses. In long term toxicity studies, NOAEL exposures are several folds higher than competitor candidate. Conclusion: Nonclinical studies demonstrated superior differentiating features of SUVN-G3031 over compounds of this class that are currently in active clinical development for the treatment of sleep related disorders. Phase-2 POC study for the treatment of narcolepsy is being planned in USA. Support (If Any): None